Adverse childhood experiences growing up in East or West Germany or abroad - Schulz, Ann-Christin; Kasinger, Christoph; Beutel, Manfred; Fegert, Jörg M.; Clemens, Vera; Brähler, Elmar (Frontiers in Psychiatry, 2022)
Background: Adverse childhood experiences (ACEs) are potentially traumatic events that occur before the age of 18. In this context, the term encompasses a wide range of adverse childhood experiences, e.g., physical, psychological and sexual abuse, physical and psychological neglect, and family dysfunction. Prevalence estimates for a broad spectrum of ACEs against the background of where childhood and adolescence were spent are scarcely available in Germany. This study examines the frequencies of adverse childhood experiences, considering growing up in East or West Germany or abroad and the interaction with different age cohorts and gender. Methods: A total of 5 018 individuals (51.4% female) aged 14 years and older were retrospectively assessed on adverse childhood experiences using questionnaires ("adverse childhood experiences," ACE). Descriptive statistics and univariate analyses were used to calculate frequencies, proportions, and unadjusted associations for each variable. Logistic regression models were used to analyze the association between birth cohort, gender, and where a person grew up. Results: 37.4% (N = 1878) of respondents reported experiencing at least one form of ACE. Individuals who grew up abroad report significantly more adverse childhood experiences than individuals in East or West Germany. Men and women who grew up in East Germany reported a lower sum rate of ACEs. We found significant effects for all predictors: Where childhood and adolescence were predominantly spent, year of birth, and gender. Significant differences in the prevalence of adverse childhood experiences within the gender groups were only found for sexual and physical abuse, and substance dependence in the household. Conclusions: The results suggest that the socio-political context plays an important role in the experience of adverse childhood experiences, both in frequency and risk. Thus, the study of child abuse and neglect should increasingly focus on societal risk and protection mechanisms.